Trisetum spicatum (Poaceae: Pooideae): an interglacial relict in the Iranian mountains - Talebi, Amir; Naqinezhad, Alireza; Attar, Farideh (Phytotaxa, 2022)
Trisetum spicatum, a widespread arctic and alpine species, is reported for the first time in the flora of Iran. This species was collected from scree habitats above 4000 m a.s.l. of Mt. Damavand (Central Alborz, Alborz range, N. Iran). This new occurrence of the species in the alpine area of Iran highlights the role of high mountains as migration corridors and refugee during interglacial periods. This new record is different from the other species by its habitat characteristics, compact inflorescence and having dense trichomes on whole parts especially on the peduncle. In addition, ecological and floristic characteristics of the habitat of the species are discussed.